2017
DOI: 10.1027/1618-3169/a000372
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cognitive Control on Different Types of Auditory Distraction

Abstract: Deviant as well as changing auditory distractors interfere with short-term memory. According to the duplex model of auditory distraction, the deviation effect is caused by a shift of attention while the changing-state effect is due to obligatory order processing. This theory predicts that foreknowledge should reduce the deviation effect, but should have no effect on the changing-state effect. We compared the effect of foreknowledge on the two phenomena directly within the same experiment. In a pilot study, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(69 citation statements)
references
References 44 publications
(78 reference statements)
6
62
1
Order By: Relevance
“…These results are consistent with the duplex-mechanism account: A forewarning eliminated the effect of a deviant because this effect is underpinned by aspecific attentional diversion caused by the violation of a predictive model. That is, the forewarning 2 Bell et al (2017) reported that the effect of a deviant was not reduced by foreknowledge and concluded that this finding "disconfirms the prediction of the duplex model that the deviation effect is more amenable to cognitive control than the changing-state effect" (p. 366). However, the deviant in Bell et al's study only produced a very small performance decrement (around 2-3%) whereas the decrement in the relevant experiment of Hughes et al (2013, Experiment 2) was around 10%.…”
Section: Predicting Distraction: the Effects Of Foreknowledgementioning
confidence: 99%
See 3 more Smart Citations
“…These results are consistent with the duplex-mechanism account: A forewarning eliminated the effect of a deviant because this effect is underpinned by aspecific attentional diversion caused by the violation of a predictive model. That is, the forewarning 2 Bell et al (2017) reported that the effect of a deviant was not reduced by foreknowledge and concluded that this finding "disconfirms the prediction of the duplex model that the deviation effect is more amenable to cognitive control than the changing-state effect" (p. 366). However, the deviant in Bell et al's study only produced a very small performance decrement (around 2-3%) whereas the decrement in the relevant experiment of Hughes et al (2013, Experiment 2) was around 10%.…”
Section: Predicting Distraction: the Effects Of Foreknowledgementioning
confidence: 99%
“…However, the deviant in Bell et al's study only produced a very small performance decrement (around 2-3%) whereas the decrement in the relevant experiment of Hughes et al (2013, Experiment 2) was around 10%. As the authors themselves have pointed out (Bell et al, 2017;Röer et al, 2015), it would be difficult to observe a benefit of foreknowledge on distraction if the amount of distraction is very small in the first place. This discrepancy in the size of the deviation effect may be due to the use of a (probably more salient) deviation in voice in Hughes et al (2013) as opposed to a word-deviation (e.g., "fall, fall, fall, dog...") in Bell et al (2017).…”
Section: Predicting Distraction: the Effects Of Foreknowledgementioning
confidence: 99%
See 2 more Smart Citations
“…If the student's anxiety increased and performed better in the ambient sound condition which was meant to elicit more anxiety, the student may have performed better because their situation was mood-congruent (DeMarco, Taylor, & Friedman, 2015) and potentially more familiar. It may have been easier to perform because they already had the expectation that other people would disrupt their performance and therefore found it easier to focus regardless of whether their anxiety was increased or decreased across conditions (Bell et al, 2017). However, if the participant came in with high anxiety they were more likely to perform worse in the ambient sound condition and better in the silence condition (see figure G2 in appendix G).…”
Section: Anxiety and Performancementioning
confidence: 92%